2019
DOI: 10.1080/09553002.2019.1554920
|View full text |Cite
|
Sign up to set email alerts
|

MRI evaluation of the effects of whole brain radiotherapy on breast cancer brain metastasis

Abstract: Purpose: To assess early changes in brain metastasis in response to whole brain radiotherapy (WBRT) by longitudinal Magnetic Resonance Imaging (MRI). Materials and methods: Using a 7T system, MRI examinations of brain metastases in a breast cancer MDA-MD231-Br mouse model were conducted before and 24 hours after 3 daily fractionations of 4 Gy WBRT. Besides anatomic MRI, diffusion-weighted (DW) MRI and dynamic contrast-enhanced (DCE) MRI were applied to study cytotoxic effect and blood-tumor-barrier (BTB) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…5). This data is consistent with increased K trans values (BBB permeability measured clinically) seen in quantitative DCE MRI in irradiated tumors at 24hrs post-irradiation (70). Broad beam radiotherapy also displayed increased BTB permeability in treated lesions (71).…”
Section: Discussionsupporting
confidence: 83%
“…5). This data is consistent with increased K trans values (BBB permeability measured clinically) seen in quantitative DCE MRI in irradiated tumors at 24hrs post-irradiation (70). Broad beam radiotherapy also displayed increased BTB permeability in treated lesions (71).…”
Section: Discussionsupporting
confidence: 83%
“…From a biological standpoint, this finding might reflect early and subtle posttreatment vasogenic edema with weakening of the blood–brain barrier, possibly explaining the previously reported effects of radiation therapy on T 1 DN‐to‐pons ratios in patients exposed to GBCAs 13,14,21 . Indeed, a recent study based on a murine model with analysis of DWI and MRI dynamic contrast‐enhanced imaging, before and 24 hours after three daily fractions of 4 Gy whole‐brain radiotherapy, showed increased ADC values together with higher permeability (parameter K trans ) in the treated metastatic tumors 30 . Moreover, another study performed with a 9.4T MRI scanner on a murine model showed a gradual increase of the ADC values among various regions of the entire brain after irradiation 31 .…”
Section: Discussionmentioning
confidence: 93%
“…Presently, one of the main mechanisms of tumor therapy is to induce apoptosis of tumor cells through various therapeutic measures [38][39][40][41][42]. Radiotherapy is a local treatment method that uses radiation to reduce or eliminate tumor lesions and is one of the commonly used methods in clinical tumor therapy [43]. In recent years, many studies have shown that radiotherapy induces apoptosis in tumor cells [44][45][46].…”
Section: Correlation Between Mir-210 and The Efficacy Of Radiotherapy For Ovarian Cancer And Its Mechanismsmentioning
confidence: 99%